Transformasi Digital Dalam Praktik Kenotariatan: Implementasi Sertifikat Elektronik Untuk Akta Otentik Berdasarkan Undang-Undang Jabatan Notaris - Maulita Tri Rosyida; Rusdianto Sesung; Habib Adjie (Journal of Innovative and Creativity, 2025)
Digital transformation has rapidly penetrated various sectors, notably including notarial practices across Indonesia. This article is dedicated to analyzing the practical implementation of electronic certificates when notaries manufacture authentic deeds. The analysis refers specifically to Law No. 2 of 2014, which amends the Notary Position Law (UUJN), and examines its relationship with the Law on Information and Electronic Transactions (UU ITE). The adoption of electronic certificates and electronic signatures (TTE) holds significant promise, aiming for efficiency, speed, and enhanced security of legal documents, fully aligning with the modern concept of "Cyber Notary". Nevertheless, this study revealed a critical finding: a normative discrepancy exists. While the UUJN still conservatively mandates physical presence and written form, the ITE Law boldly acknowledges the validity of electronic documents. This regulatory gap is consequential. The absence of explicit regulations concerning electronic authenticated deeds created by notaries directly results in legal uncertainty regarding the deed's strength of proof. Consequently, we assert the urgent need for harmonizing regulations. Developing an integrated digital infrastructure is also vital to guarantee legal certainty and protection for both the public and notaries as they navigate the digital era.